SASTRA ANAK BERBASIS ETNOMATEMATIK SEBAGAI MEDIA PENANAMAN WAWASAN DAERAH - Dewi Fitriana (Tunas Nusantara, 2019)
The children’s’ literature is a form of imaginative creation with language exposure that describes the world of fiction, presents understanding and experience and contains aesthetic value. The children's literature is synonymous with cultural elements, namely fairy tales or legends. The development of culture itself is inseparable from the discipline of mathematics. The cultural relationship with mathematics is a scientific discipline called ethnomathematics. The children’s literary based ethnomathematics forms influence the knowledge of regional insights and the ability to think critically mathematics. The role of children's literature based ethnomathematics developed in a modern way through comics or fairy tales, gives enthusiasm for reading and knowledge of regional insights, namely local languages, traditional houses, special foods, and others